OMAX testing of a bow-string and a stress-ribbon footbridge - Edwin Reynders (2008)
A recent development in Operational Modal Analysis (OMA) is the possibility to use measured, artificial forces as an addition to the unmeasured, ambient excitation. This combined experimental-operational or OMAX approach (Operational Modal Analysis with eXogenous forces), requires special system identification algorithms, that take both the ambient and the forced excitation into account. The ambient excitation is not considered as noise, as it is in Experimental Modal Analysis (EMA), but as a valuable yet unmeasured part of the excitation, so that the ratio between forced and ambient excitation can be much lower than in classical EMA testing. The modes that are (partly) excited by the measured forces can be scaled in an absolute way, e.g., to unity modal mass. The combined modal testing of footbridges is explored using two case studies: a steel arch footbridge with spans of 75.2m and 30.3m and a concrete stress-ribbon footbridge with spans of 30m and 28m. The modal parameters (eigenfrequencies, damping ratios, mode shapes and modal scaling factors), obtained from a combined vibration test, are compared with the ones obtained from other modal tests and from a finite element model. The comparison demonstrates the feasibility of using small, cheap, and practical actuators for the OMAX testing of footbridges, as opposed to the heavy, expensive, and impractical actuators such as electromechanical or hydraulic shakers that usually have to be used for EMA testing of civil engineering structures.